Integrating Multicultural Children's Math Books Into Kindergarten Through Sixth-Grade Classrooms: Preservice Teachers' Reflections. Issue 4 (2nd October 2017) - Harding, Jenni; Hbaci, Ilham; Loyd, Stacy; Hamilton, Boni
ABSTRACT: This case study of mathematics instruction using children's literature reports on the experiences 47 elementary preservice teachers had in their mathematics methods course while completing a microteaching assignment. As part of the microteaching assignment, preservice teachers were required to plan and teach mathematics lessons based on children's books that included both mathematics concepts and multicultural aspects. The preservice teachers audio-recorded their lessons, transcribed the audio, and wrote reflective essays to articulate their experiences. At the end of the assignment, the professor and two additional researchers interviewed the preservice teachers about their experiences. Themes that emerged were (a) teaching experiences, (b) teaching performance, and (c) learning purposes and tools for integrating multicultural children's math books. The Learning Purposes and Teaching Strategies for Integrating Multicultural Mathematics Picturebooks Framework was developed to demonstrate the intricate balance needed to ensure mathematics learning happens during instruction with multicultural mathematics picturebooks.